Perubahan Fungsi Lansekap Terhadap Peningkatan Temperatur Udara di Lingkungan Kota Makassar - Juhana Said (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
The growth of the city very quickly in a relatively short period. Their demands of facilities and infrastructure, the demand for shopping centers, mall, new residential areas, industrial areas, and others led to increasingly dense urban land. The number of smaller plots of open land increasingly pressing. Function changes the landscape certainly has an impact on the increase in air temperature and the formation of heat islands in urban areas. This paper focuses will see changes in the landscape functions that occur in the city of Makassar from several decades. The changing landscape in this case is a change in land use and function of landscapes, include: developed and undeveloped land (housing, shops, offices, government buildings, public facilities, etc.), open land (garden / field), land aqueous (ponds, marshes, rivers, reservoirs and canals), arable land (paddy), and green land (garden and forest). Function changes the landscape of the open area into the city closed and dense, reflecting the high temperatures in the neighborhood. To obtain accurate data do support the relevant documentation, related; land cover data, interpretation of historical maps, aerial photographs and the collection of statistical data.